MODEL PEMBELAJARAN COOPERATIVE LEARNING UNTUK MENINGKATKAN MINAT DAN KREATIVITAS BELAJAR SISWA KELAS KHUSUS - Irawan Irawan; Abd. Munif; Risma Putri Artama; Joan Hesti Gita Purwasih (Jurnal Visi Ilmu Pendidikan, 2022)
Every learning process has its own challenges, one of which is due to the conditions and learning programs pursued by students. For example in the special class ASIFA foundation in collaboration with SMAN 7 Malang. There is a special class of soccer athletes studying at the school, namely in class XI IPS 6. Students in the class have programs in the field of sports that are quite high. Meanwhile, the results of observations and interviews indicate that the development of learning innovations through models and types of media is still not much developed by teachers. The impact, there are symptoms of low interest and lack of creativity in students. Therefore, researchers try to address these problems by conducting classroom action research using Jigsaw models accompanied by comic-making activities in the learning process. The results show that the level of student interest in learning and creativity has increased. In cycle one, there was an average increase of interest of 62%. Meanwhile, in the second cycle there was an increase in interest on average by 74%.